2020
DOI: 10.1371/journal.ppat.1008576
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia pseudotuberculosis YopH targets SKAP2-dependent and independent signaling pathways to block neutrophil antimicrobial mechanisms during infection

Abstract: Yersinia suppress neutrophil responses by using a type 3 secretion system (T3SS) to inject 6-7 Yersinia effector proteins (Yops) effectors into their cytoplasm. YopH is a tyrosine phosphatase that causes dephosphorylation of the adaptor protein SKAP2, among other targets in neutrophils. SKAP2 functions in reactive oxygen species (ROS) production, phagocytosis, and integrin-mediated migration by neutrophils. Here we identify essential neutrophil functions targeted by YopH, and investigate how the interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 109 publications
2
48
0
Order By: Relevance
“…Neutrophils play an important role in host defence against Yersinia infection (25,26) and are the most abundant cell type that are injected with effector proteins during Yersinia infection (27). Therefore, we next examined the contribution of GSDMD and GSDME to neutrophil cell lysis and cytokine secretion following Yptb infection.…”
Section: Gsdme But Not Gsdmd Promotes Apoptotic Neutrophil Cell Lysismentioning
confidence: 99%
“…Neutrophils play an important role in host defence against Yersinia infection (25,26) and are the most abundant cell type that are injected with effector proteins during Yersinia infection (27). Therefore, we next examined the contribution of GSDMD and GSDME to neutrophil cell lysis and cytokine secretion following Yptb infection.…”
Section: Gsdme But Not Gsdmd Promotes Apoptotic Neutrophil Cell Lysismentioning
confidence: 99%
“…Neutrophil ROS production is driven by signal transduction pathways downstream of several receptors, including integrin, Dectin-1, Fcγ, and G-protein-coupled receptors (GPCRs), that activate the components of the NADPH oxidase complex (Nguyen et al, 2017). Recently, we and others reported that S rc K inase A ssociated P hosphoprotein-2 (SKAP2) was essential for ROS production in response to stimulation by integrin and GPCRs, as well as gram-negative bacteria K. pneumoniae and Yersinia pseudotuberculosis (Nguyen et al, 2020, Shaban et al, 2020, Boras et al, 2017). In addition, SKAP2 is critical for integrin-stimulated cytoskeletal changes in macrophages and neutrophils (Alenghat et al, 2012, Tanaka et al, 2016, Boras et al, 2017), and for K. pneumoniae -mediated Syk phosphorylation in neutrophils (Nguyen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SKAP2 is critical for integrin-stimulated cytoskeletal changes in macrophages and neutrophils (Alenghat et al, 2012, Tanaka et al, 2016, Boras et al, 2017), and for K. pneumoniae -mediated Syk phosphorylation in neutrophils (Nguyen et al, 2020). Further highlighting the role of SKAP2 in the innate immune response, Skap2-/- mice are more susceptible to K. pneumoniae , exhibiting a higher K. pneumoniae bacterial burden than wild-type controls (Nguyen et al, 2020) and SKAP2 is an essential target of the virulence factor, YopH, in neutrophils during Y. pseudotuberculosis infection (Shaban et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations